(3fXe GdeYdheGJ GdeMGSHjIs - (3GdOgQGhj(B, (3ceGd GdOjf eUWais; (3SejQ cGeds ((3GdEScfOQjIs (3OGQ GdLGeYI GdLOjOIs, 2002)
(3GdeaGgje GdGSGSjI dfXe GdeYdheGJ , JTZjd GdeYdheGJ aj fXGe GdeYdheGJ GdeMGSHj, OhQGJ GdYedjGJ(B- (3fXe GdeYdheGJ GdbGFeI Ydi GdMGSHGJ GdEdcJQhfjI GdeJbOeIs
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJs